PENGARUH METODE PEMBELAJARAN EXPLICIT INSTRUCTION TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PEMROGRAMAN WEB DINAMIS KELAS XI JURUSAN REKAYASA PERANGKAT LUNAK (RPL) DI SMK NEGERI 1 SINTUK TOBOH GADANG - Dewi Sismira Yumiarti; Efrizon Efrizon; Asrul Huda (Universitas Negeri Padang, 2018)
The purpose of this research is to reveal the magnitude of the percentage of the influence of the application of explicit instruction learning method with direct learning model on the subjects of Dynamic Web Programming class X1 Software Engineering semester odd SMK Negeri 1 Sintuk TobohGadang Year Teaching 2016/2017. This type of research is quantitative using experimental type quasi experimental design research method. This research was conducted at SMK Negeri 1 SintukTobohGadang on 17 july until 17 august 2017. Population in this research that is student of class X1 RPL SMK Negeri 1 SintukTobohGadang. Sampling technique used is probability sampling with simple random sampling technique. The selected to be samples in this study are students of class X1 RPL2 experimental class and X1 RPL1 as control class. Based on the result of the research, the average of learning result of the experimental class is 82,48, while the control class get the average value 77,75. The result of hypothesis calculation at significant level α = 0,05 got tcount>ttable that is (2,278> 1, 677), because big tcount of ttable, null hypothesis (H0) rejected and alternative hypothesis (Ha) accepted. This means that explicit instruction learning method has a positive effect on the learning outcomes Dynamic Web Programming students of class X1 SMK Negeri 1 SintukTobohGadang. Keywords:Learning outcomes, explicit instruction learning methods, direct learning models